Ethical attitude in the opinion of pediatric nurses - Paszkiewicz-Mes, Emilia; Głowacka, Agnieszka; Grzanek, Marzena; Mielczarek, Jadwiga; Lewandowska, Małgorzata; Brosowska, Beata (Nursing in the 21st Century, 2016)
ETHICAL ATTITUDE IN THE OPINION OF PEDIATRIC NURSES Introduction. Behaviour according to the ethical principles is meaningful for shaping of nurses’ ethical and professional attitude. Contact between the nurse and the sick child requires an ethical model and professional attitude, excellent politeness and sensitivity. Aim. Assessment of ethical attitudes in the opinion of pediatric nurses. Material and method. Research was conducted among 133 nurses working in two hospitals in Łodz: in the Clinical Hospital No. 4 of Medical University and in the Institute of Polish Mother’s Health Center. The study used questionnaire of own design. Pearson correlation index determination was used for statistical analysis of the results. Results and conclusions. More than half examined nurses (63.4%) was able to give a correct definition of professional ethics. The nursing profession was not connected only with earnings in the opinion of 86.4% nurses. Most respondents (56.8%) have admitted that nurses not always behave ethically. Too low salary was the most often mentioned reason (67%) for not ethical behaviour. High sense of responsibility and patience are the main features which mus distinguish the nurse. More than half of the respondents would choose this profession again. Participants claimed most often (95.5%) that nurses should deepen their knowledge permanently, but not everyone even in this group, does it.